'Somehow, We Cannot Accept It': Drivers of Internal Displacement from Crimea and the Forced/Voluntary Migration Binary. Issue 3 (15th March 2020) - Charron, Austin
Abstract: Overshadowed by their far more numerous counterparts from Donbas, Crimean IDPs have been under-examined and misunderstood. Relying on interviews and focus groups conducted amongst Crimean IDPs, the essay traces the experiences and conditions of Russian occupation that have triggered the migration of Crimeans to mainland Ukraine since 2014. Pointing to how both structural forces and human agency are at play in the political, socio-economic and emotional factors driving their displacement, this essay argues that migration from occupied Crimea to mainland Ukraine—like all migrant flows—is neither exclusively forced nor entirely voluntary.